The Influence of Lavender Aroma Therapy on Decreasing Blood Pressure in Hypertension Patients - Agustina Boru Gultom; Surita Ginting; Elni Lorensi Silalahi (Intelektual Pustaka Media Utama, 2016)
The objective of this research was to determine the influence of lavender aromatherapy on decreasing blood pressure in hypertension patients. The research employed quantitative method with quasi experiment design. The samples were 32 patients either in the treatment group or in the non-treatment group. They were selected by consecutive sampling technique. The result of the research showed that the decrease in systolic and diastolic blood pressure of the treatment group was 9.7299 mmHg and 4.3237 mmHg while without treatment was 7.0461 mmHg and 3.51152 mmHg. Paired t-test resulted the probability value of systolic blood pressure was α (0.000) <0.05, the probability of diastolic blood pressure was α (0.000) <0.05. It could be concluded that there was the influence of lavender aromatherapy on the decrease in systolic and diastolic blood pressure. Inhalation with lavender aromatherapy method can become one of the considerations in nursing intervention to decrease blood pressure in hypertension patients. It can be an alternative of therapy complement besides medication.